PERAN TRI PUSAT PENDIDIKAN (KELUARGA, SEKOLAH, DAN MASYARAKAT) DALAM UPAYA PENGEMBANGAN SUMBER DAYA MANUSIA YANG BERKUALITAS - Maarifudin (Jurnal El-Hamra : Kependidikan dan Kemasyarakatan, 2017)
Education becomes the foundation in shaping and instilling human values in learners as part of life process in family, society, nation and state. Tri education centers in the form of family environment, school environment and community environment plays a very important role in relation to the progress of building a community order. Because the family environment becomes the first basic education for children before entering school, the school environment also influences in obtaining knowledge of the skills and skills possessed, while the community contribute in the formation of behavior through existing norms and culture. In this way, the education center is a solid building between elements of one with other elements in which they are interrelated and influencing. Like a link, if a decrease in the family position it will trigger an impact on the school stage and walk up to the community.Key Words: Tri Education Center, SDM, character